Insulin Sensitizing and Antiatherogenic Role of Adiponectin: A Cross Sectional Study among the Healthy Subjects in Kerala - Sudharmadevi, Dr. Manju K; Balakumaran, Dr. Leena K; Lekshminarayan, Dr. Vijayalekshmi; Trivikrama, Dr. Shenoy K (International Journal of Innovative Research in Medical Science, 2021)
Background of the study and objectives: Adiponectin, the most abundantly secreted adipokine plays a central role in energy homeostasis. Different studies have reported the protective role of adiponectin in obesity related complications such as insulin resistance, hypertension, dyslipidemia, atherosclerosis etc. Since not much studies were conducted to analyze the role of adiponectin in the metabolic homeostasis among the healthy population in Kerala, we designed this study. Materials and methods: This study included 170 healthy subjects of both gender in the age group of 20-60 years. Anthropometric measurements and blood pressure were recorded. BMI, WHR and BF% were calculated. Fasting blood sample was used to measure glucose, lipid profile, insulin and adiponectin. HOMA-IR, HOMA-β and QUICKI were calculated. Data was analyzed by student’s ‘t’ test and pearson’s correlation analysis. p <0.05 was considered statistically significant. Results: Serum adiponectin showed a negative correlation with BMI (r=-0.583) and body fat percentage (r=-0.369). An inverse significant correlation of adiponectin with serum triglycerides (p=0.01), fasting glucose (p=0.01) and HOMA-IR (p=0.001) was observed. But insulin sensitivity (QUICKI) (p=0.001) and serum HDL-cholesterol (p=0.01) showed a significant positive correlation with adiponectin. Analysis of the study subjects based on BMI showed a significant decrease in serum adiponectin (p=0.001) among obese group in comparison with normal weight subjects. Hypoadiponectinemia among obese subjects was also found to be associated with insulin resistance and decreased insulin sensitivity expressed as QUICKI. Conclusion: Serum adiponectin showed a positive correlation with insulin sensitivity and HDL-cholesterol. Adiponectin retains a significant role as a mediator of insulin resistance and atherosclerosis.